2011
DOI: 10.2166/wh.2011.114
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological assessment of drinking water supply options in coastal areas of Bangladesh

Abstract: This study was conducted to assess the bacteriological quality of alternative drinking water supply options in southwest coastal areas of Bangladesh. A total of 90 water samples were collected during both dry and wet seasons from household based rainwater harvesting systems (RWHSs), community based rain water harvesting systems (CRWHSs), pond-sand filters (PSFs) and ponds. The samples were evaluated for faecal coliform, Escherichia coli and Heterotrophic Plate Count, as well as Vibrio cholerae, Salmonella spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 19 publications
5
41
0
Order By: Relevance
“…Rain-feed pond waters are highly polluted due to unhygienic sanitation in and around the pond, indiscriminant usage and lack of protection of the ponds. The FC and E.coli counts were found to vary from 12 to 10,000 and zero to 3000 per 100 mL (Islam et al 2011), respectively, together with the presence of several pathogenic bacteria. Several studies (Islam et al 2011;Karim 2010;Howard et al 2006;Ahmed et al 2005) in Bangladesh showed that the rooftop harvested rainwater was also microbiologically contaminated to a great extent, which may cause significant health risks of the rural people.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 4 more Smart Citations
“…Rain-feed pond waters are highly polluted due to unhygienic sanitation in and around the pond, indiscriminant usage and lack of protection of the ponds. The FC and E.coli counts were found to vary from 12 to 10,000 and zero to 3000 per 100 mL (Islam et al 2011), respectively, together with the presence of several pathogenic bacteria. Several studies (Islam et al 2011;Karim 2010;Howard et al 2006;Ahmed et al 2005) in Bangladesh showed that the rooftop harvested rainwater was also microbiologically contaminated to a great extent, which may cause significant health risks of the rural people.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…The FC and E.coli counts were found to vary from 12 to 10,000 and zero to 3000 per 100 mL (Islam et al 2011), respectively, together with the presence of several pathogenic bacteria. Several studies (Islam et al 2011;Karim 2010;Howard et al 2006;Ahmed et al 2005) in Bangladesh showed that the rooftop harvested rainwater was also microbiologically contaminated to a great extent, which may cause significant health risks of the rural people. Studies from other countries (Despins et al 2009;Sazakil et al 2007;Meera and Ahammed 2006) also reported microbial contamination of harvested rainwater and consumption of the water may cause a variety of infectious diseases around the world (Lye 2002).…”
Section: Accepted Manuscriptmentioning
confidence: 96%
See 3 more Smart Citations